The Influence of Interleukin 17A and IL17F Polymorphisms on Chronic Periodontitis Disease in Brazilian Patients - Joana Maira Valentini Zacarias; Emília Ângela Sippert; Patrícia Yumeko Tsuneto; Jeane Eliete Laguila Visentainer; Cléverson de Oliveira e Silva; Ana Maria Sell (Mediators of Inflammation)
A case-control study was conducted on patients with chronic periodontitis (CP) and healthy controls with the aim of evaluating possible association between interleukin 17A (IL17A) G197A (rs2275913) and IL17F T7488C (rs763780) polymorphisms and periodontitis. Genotypes were determined by PCR-RFLP method. Statistical analyses were conducted using the OpenEpi and SNPStas software to calculate Chi-square with Yates correction or Fisher’s exact tests, odds ratios (OR), and 95% confidence intervals (CIs). SNPStas software was used to calculate Hardy-Weinberg equilibrium. IL17A AA genotype was more frequent in patients with chronic periodontitis (CP) in the codominant and recessive models (P=0.09; OR = 2.53 and P=0.03; OR = 2.46, resp.), the females with CP (P=0.01, OR = 4.34), Caucasoid patients with CP (P=0.01, OR = 3.45), and nonsmoking Caucasian patients with CP (P=0.04, OR = 3.51). The IL17A A allele was also more frequent in Caucasians with CP (P=0.04, OR = 1.59). IL17F T7488C polymorphism was not associated with chronic periodontitis. In these patients from Southern Brazil, the IL17A rs2275913 polymorphisms, IL17A AA genotype, and the A allele were associated with a susceptibility to chronic periodontitis.